Improving Science Learning Outcomes Through Online Learning Model E-Learning With Video Media - Paizar, Paizar (Yayasan Corolla Education Centre, 2021)
This study uses Classroom Action Research (CAR) in the form of implementing an e-learning model with video media to improve the learning outcomes of fourth-grade students at SD Negeri 3 Epil which consists of two cycles and each cycle consists of planning, implementing, observing, and reflecting. The research subjects were fourth-grade students of SD Negeri 3 Epil. The number of students is 29 students consisting of 10 male students and 19 female students. The results showed that the application of the e-learning model with video media could improve science learning outcomes in fourth-grade students of SD Negeri 3 Epil. Judging from the results of pre-cycle students who completed KBM only 14 students (48.3%) and 15 students (51.7%) had not. In the first cycle there are 24 students (82.8%) who have completed and 5 students (17.2%) have not completed, and in the second cycle, there are 26 students (89.7%) who have completed and there are 3 students (10.3 %) unfinished. From the increase in learning outcomes, this classroom action research was stopped in cycle II because it had reached the classical completeness criteria, namely 85% of the total number of students who had completed learning and were declared successful in improving science learning outcomes in Grade IV students of SD Negeri 3 Epil Academic Year 2020/ 2021.